Genetic Differentiation by Nucleic Acid Homology IV. Relationships Among Lancefield Groups and Serotypes of Streptococci - Weissman, Sherman M. (1966)
Weissman, Sherman M. (National Cancer Institute, Bethesda, Md.), Paul R. Reich, Norman L. Somerson, and Roger M. Cole. Genetic differentiation by nucleic acid homology. IV. Relationships among Lancefield groups and serotypes of streptococci. J. Bacteriol. 92:1372–1377. 1966.—A deoxyribonucleic acid-ribonucleic acid homology technique was used to measure the genetic relatedness among Lancefield groups and serotypes of streptococci. Organisms in different Lancefield groups were related, but were differentiated from each other. Serotypes within group A could be distinguished. Two isolates serologically classified in group A type 1 were indistinguishable. Streptococcus faecalis was only remotely related to streptococci of Lancefield groups A and H, whereas Diplococcus pneumoniae was more closely related to these organisms. The serological data were in good agreement with the results obtained with the homology method.